Cerebral hemodynamics in patients with arterial hypertension of the older age groups with orthostatic hypotensive reactions. (25th November 2020) - Atyunina, I; Oschepkova, E; Rogoza, A; Lazareva, N
Abstract: Objective: To study cerebrovascular autoregulation in pts with arterial hypertension (AH) with orthostatic hypotensive reactions (OHR) during an active orthostatic test (AOT). 50 pts with AH (40 g, 10 m), 68.5±5.3 years, I-III gr. were examined. Blood pressure monitoring (BPM) by "BP Lab", Russia. AOT was performed with continuous measurement of systolic blood pressure (SBP) and diastolic blood pressure (DBP) in the digital artery ("Task Force Monitor", "CNSystems" Austria). The criteria for the OHR were evaluated according to guidelines ESC, 2018. Cerebral hemodynamics in the middle cerebral artery (MCA) was monitored during the AOT (Angiodin-2K (BIOSS company, Russia), using a transcranial sensor with a freq. of 2 MHz. In the MCA, systolic (Vs), diastolic (Vd), average cerebral blood flow velocity (Vm), pulsation index (Pi), and vascular resistance index (Ri), the difference ΔVm30s, % and ΔVm30s, were recorded. Statistical analysis was performed using the non-parametric Mann-Whitney method using Statistica 6.0 Results: In 17 (34%) pts with AH, OHR was detected. BP in pts with OHR compared with pts without OHR (mmHg), SBP: 131.7±12.2 vs 131.3±13.8, p>0.05; DBP 74.3±11.8 vs 75.3±8.9, p>0.05). In AOT in pts with OHR, the Vm in the orthostasis significantly decreased compared to pts without OHR, both in the first 30 s. and at 3 min. (Tabl.1). Conclusions: In pts with AH of older age groups with OHR, in comparison with the same category of pts without OHR, there is a change in cerebral autoregulation in the form of a more pronounced decrease in cerebral blood flow velocity in MCA in the orthostatic position. Funding Acknowledgement: Type of funding source: None